Telorta divergens ... - Dubatolov, V. V.; Zinchenko, V. K; Ustjuzhanin, P. Ya. (Zenodo, 2023)
Telorta divergens (Butler, 1879) MATERIAL. Russia: Kunashir Island, Andreevskii kordon, 18-25.IX, 29.IX-7.X, 15- 19.X, 25.X 2022, 8 ♂, 17 ♀, 6 spm.; Danilovskii kordon, 25-27.IX, 2.X, 7-14.X 2022, 3 ♂, 4 ♀, 3 spm.; Yuzhno-Kurilsk, 27-29.IX 2022, 1 ♂, 1 ♀. DISTRIBUTION. Russia: Jewish Autonomous Oblast’, south part of Khabarovskii krai, north to Komsomolsk-na-Amure, Primorskii krai (Kononenko, 2016), Sakhalin (Dubatolov et al., 2020); Japan: Hokkaido, Honshu, Shikoku, Kyushu; Korea, China (Eda & Shikata, 2011). ... : Published as part of Dubatolov, V. V., Zinchenko, V. K & Ustjuzhanin, P. Ya., 2023, Autumn moths and butterflies (Lepidoptera) new for the fauna of Kunashir Island, pp. 11-24 in Far Eastern Entomologist 474 on page 19, DOI: 10.25221/fee.474.3, http://zenodo.org/record/7945971 ...